Social transfer programmes and school enrolment in Malawi: A micro-simulation - Malokele Nanivazo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper investigates the impact of social transfer programmes on school enrolment and child labour in Malawi utilizing a micro-simulation evaluation method. Four hypothetical cash transfer programmes, differentiated in terms of their conditions on children's enrolment and gender, are considered. Results show that boys' enrolment increases in all four scenarios, whereas girls' enrolment increases only when the conditionality on enrolment is enforced.
Keywords: H53; I38; J22; I2; 330; Malawi; social safety nets; social transfer programmes; micro-simulation; education